Improved ferroelectric/piezoelectric properties and bright green/UC red emission in (Li, Ho)-doped CaBi4Ti4O15 multifunctional ceramics with excellent temperature stability and superior water-resistance performance. Issue 39 (21st September 2015) - Xiao, Ping; Guo, Yongquan; Tian, Mijie; Zheng, Qiaoji; Jiang, Na; Wu, Xiaochun; Xia, Zhiguo; Lin, Dunmin
Abstract : Multifunctional materials based on rare earth ion doped ferro/piezoelectrics have attracted considerable attention in recent years. Abstract : Multifunctional materials based on rare earth ion doped ferro/piezoelectrics have attracted considerable attention in recent years. In this work, new lead-free multifunctional ceramics of Ca1− x (LiHo) x /2 Bi4 Ti4 O15 were prepared by a conventional solid-state reaction method. The great multi-improvement in ferroelectricity/piezoelectricity, down/up-conversion luminescence and temperature stability of the multifunctional properties is induced by the partial substitution of (Li0.5 Ho0.5 ) 2+ for Ca 2+ ions in CaBi4 Ti4 O15 . All the ceramics possess a bismuth-layer structure, and the crystal structure of the ceramics is changed from a four layered bismuth-layer structure to a three-layered structure with the level of (Li0.5 Ho0.5 ) 2+ increasing. The ceramic with x = 0.1 exhibits simultaneously, high resistivity ( R = 4.51 × 10 11 Ω cm), good piezoelectricity ( d 33 = 10.2 pC N −1 ), high Curie temperature ( T C = 814 °C), strong ferroelectricity ( P r = 9.03 μC cm −2 ) and enhanced luminescence. These behaviours are greatly associated with the contribution of (Li0.5 Ho0.5 ) 2+ in the ceramics. Under the excitation of 451 nm light, the ceramic with x = 0.1 exhibits a strong green emission peak centered at 545 nm, corresponding to the transition of the 5 S2 → 5 I8 level in Ho 3+ ions, while a strong red up-conversion emission band located at 660 nm is observed under the near-infrared excitation of 980 nm at room temperature, arising from the transition of 5 F5 → 5 I8 levels in Ho 3+ ions. Surprisingly, the excellent temperature stability of ferroelectricity/piezoelectricity/luminescence and superior water-resistance behaviors of piezoelectricity/luminescence are also obtained in the ceramic with x = 0.1. Our study suggests that the present ceramics may have potential applications in advanced multifunctional devices at high temperature.